BATting Multilingual Primary Progressive Aphasia for Greek, English, and Czech - Kambanaros, Maria; Grohmann, Kleanthes K. (My University, 2012)
We report and compare results from the Bilingual Aphasia Tes (BAT) in three languages in a multilingual individual with a fluent primary progressive aphasia (PPA): Greek, English, and Czech. Our participant, SG, is a 60-year-old male who shows focal atrophy of the left temporal and parietal lobes typical of PPA. He is highly educated and holds a full-time job in computer maintenance. He has relative preservation of memory and appropriate social behavior, and he carries out most activities of daily living, including driving, without assistance. Prior to his illness he was highly proficient, in speaking/hearing as well as reading/writing, in Greek (both the local, sociolinguistically ‘low’ variety of Cypriot Greek and the ‘high’ Standard Modern Greek), English, and Czech. All languages were used on a daily basis for different environments (such as home, work, and travel). Assessment on the BAT across languages reveals difficulties with auditory comprehension for complex items, semantic interpretation, and (morpho)syntactic operations, but generally preserved repetition, reading, and writing.
Keywords: Bilingual Aphasia Test; Dialects; Language deterioration/loss; Sentence comprehension